INDEPENDENSI AUDITOR DI MASA PANDEMI COVID-19 (STUDI PADA KAP "X" MALANG) - Ica Nur Hayani; Agustinus Rinto; Irenius Iyel; Hendrik Suhendri (Akuntansi dan Teknologi Informasi, 2022)
The Covid-19 pandemic has implications for business activities in general and has implications for the Public Accounting Firm (KAP) business, especially in terms of an auditor's independence. Meanwhile, independence is generally related to the ability of an auditor to be impartial and not easily influenced by certain parties to support audit quality during the Covid-19 Pandemic. This study aims to determine the auditor’s perception of independence during the Covid-19 Pandemic at KAP “X” Office. The paradigm in this study is the Interpretive Paradigm. This type of research is a qualitative approach. Data collection techniques using the method of observation, interviews and documentation. Test the validity of the data using the source triangulation method. The stages in this research are using data reduction, data presentation and concluding (verification). The results showed a statement from one of the informants who stated that there was a request from the client who asked the KAP auditor “X” to give a fair opinion so that there was a continuity of cooperation with the client. Based on this statement, it can be interpreted that during the Covid-19 Pandemic, there was pressure from the client on the auditor to give a fair opinion on the company’s financial performance. Therefore, the auditor needs to consistently adhere to the principle of independence to maintain the audit quality of the financial statements.